Romanian dentists' perception of flexible removable partial dentures - Georgiana Dragomir; Alexandru Titus Farcasiu; Iulia Pascal (Amaltea Medical Publishing House, 2021)
Introduction. A flexible partial denture, as a treatment solution for partial edentulousness, is a current alternative in dental prosthetics, due to simplified design, aesthetic and biomechanical qualities of resin materials, that contribute to the favourable distribution of masticatory forces on the dental and mucosal support. Objective. This study aims to highlight the medical perception of Romanian dentists regarding the evolution of patients treated with flexible partial dentures. Material and method. The research was carried out over a period of two years (2017-2019), on a study group composed of 84 Romanian dentists. Subjects were asked to answer an anonymous questionnaire consisting of 14 closed questions, to outline frequently aspects encountered in practice related to the clinical evolution of the patient rehabilitated with flexible partial removable dentures. Outcomes. Patient comfort (76%) and higher aesthetic properties (54%) were the main reasons why dentists chose a partially flexible prosthetic for the prosthetic treatment of the patient. In the evolution of prosthetic patient, the main problems found at the partial flexible prosthesis were food pigment impregnation of the base (51%) and limited possibilities of repair (34%). Changes in maintenance, support, stability, aesthetic or possible fractures of base and clasps were seen by 46% of respondents, at approximately 1 to 2 years after the application of flexible partial dentures. Conclusions. Flexible partial prosthesis is a method of treatment, whose main advantages are represented by esthetics and superior adaptation of the patients, but because of the deficiencies that occur over time, it is better to be recommended as a provisional treatment solution.